2019
DOI: 10.1177/0023677219855102
|View full text |Cite
|
Sign up to set email alerts
|

Fasting is not required for measuring plasma lipid levels in rabbits

Abstract: Plasma lipid and glucose levels are important parameters for evaluating the onset and development of metabolic and cardiovascular diseases. In clinical and experimental studies of humans or mice, fasting is often required before testing plasma lipid and glucose levels. The rabbit is a valuable animal model for cardiovascular disease research. However, whether fasting is necessary for measuring plasma lipid and glucose levels in rabbits remains unclear. In the current study, 12 healthy Japanese white rabbits (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…There was no difference in serum LDL‐cholesterol levels between the rabbits immunized with hnHDL and those that received an injection of IFA, and these levels were within normal limits for rabbits 17 . Blood HDL‐cholesterol levels in hnHDL‐immunized rabbits were higher than in the rabbits that had received an injection of IFA (Figure 5B).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…There was no difference in serum LDL‐cholesterol levels between the rabbits immunized with hnHDL and those that received an injection of IFA, and these levels were within normal limits for rabbits 17 . Blood HDL‐cholesterol levels in hnHDL‐immunized rabbits were higher than in the rabbits that had received an injection of IFA (Figure 5B).…”
Section: Resultsmentioning
confidence: 90%
“…The increase in HDL cholesterol is comparable to that observed in rabbits fed a high-cholesterol diet. 17 The cause of the increase in blood HDL cholesterol in hnHDL-immunized rabbits may be a compensatory response to the removal from the blood of HDL opsonized with anti-HDL antibodies present in the blood of immunized rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature approach to the lipid profile, which is adopted in many countries such as the USA, Switzerland, and Canada, there is no significant difference between fasting and nonfasting status, and thereby many countries make changes to their reference intervals [5,15]. A recent prospective study by Wang et al [16] evaluated lipid profile values in fasting and 4-h postprandial status. The results showed that there were no significant differences in lipid levels between the fasting and nonfasting samples.…”
Section: Discussionmentioning
confidence: 99%
“…The mean values for HDL-C and TC were very close to each other, where the highest differences between the mean values were 1.69 and 3.4 mg/dL, respectively (Table 1). Several studies have shown that fasting is not substantially necessary for routine lipid level measurements [3,16,17]. As a result of studies including children, women, and men with diabetes from the USA, Denmark, and Canada, plasma lipids and lipoproteins have been observed to change slightly in response to the patient's usual food intake (p>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Дослідження виконані на статевозрілих самцях кролів породи Hyla (n=14). У роботі були використані самці кролів, для уникнення впливу естрогенів на показники ліпідного метаболізму за рекомендацією Wang et al (2019) [13]. Групи були сформовані за принципом аналогів, по 7 тварин у кожній.…”
unclassified